2022
DOI: 10.52911/itall.1194260
|View full text |Cite
|
Sign up to set email alerts
|

Kitlesel Açık Çevrimiçi Ders Ortamlarında Öğrenci Katılımı

Abstract: Günümüzde artan nüfus, hayat boyu eğitime verilen önemin artması, sürekli eğitim ihtiyacı gibi faktörler eğitim ortamlarının değişime uğramasına yol açmıştır. Özellikle zaman ve mekan konusunda sınırlılıkları olan eğitim isteklileri için kitlesel açık çevrimiçi dersler ve uzaktan eğitim ortamları büyük kolaylık sağlamaktadır. Ancak literatürde kitlesel açık çevrimiçi ortamlarda sıklıkla kursu tamamlayamama ve katılımın azalması gibi olumsuz durumlar belirtilmiştir. Buradan yola çıkarak Web of Science veri taba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The current situation has revealed that students may encounter various challenges in the realm of online education. These challenges encompass technological obstacles, such as the absence of essential electronic tools, as well as pedagogical challenges, internal (loyalty, cooperation) and external (gamification, feedback) factors (Uçar and Sarıtepeci, 2022) including deficiencies in digital skills among both teachers and students. Additionally, social difficulties may arise due to the limited human interaction between teachers and learners in the online learning environment (Ferri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current situation has revealed that students may encounter various challenges in the realm of online education. These challenges encompass technological obstacles, such as the absence of essential electronic tools, as well as pedagogical challenges, internal (loyalty, cooperation) and external (gamification, feedback) factors (Uçar and Sarıtepeci, 2022) including deficiencies in digital skills among both teachers and students. Additionally, social difficulties may arise due to the limited human interaction between teachers and learners in the online learning environment (Ferri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%